THE INFLUENCE OF MOTIVATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PERUMDA AIR MINUM TIRTA SEWAKADARMA DENPASAR CITY - Putra, Adhy Kusuma (JURNAL ASIK, 2024)
The purpose of this study was to determine the influence of motivation and work environment on the performance of employees of Perumda Air Minum Tirta Sewakadarma Denpasar City. The research method used in this research is descriptive with a quantitative approach. The population amounted to 63 people, so the sampling technique was used with the saturated sample method and the number of samples obtained in this study were 63 respondents. Data analysis techniques using multiple linear regression.             The results showed that: (1) There is a positive and significant influence of motivation variables on the performance of employees of Perumda Air Minum Tirta Sewakadarma Denpasar City. This is evidenced by the value of tcount > ttable, namely 7.050 > 2.000 with a probability value (significance) = 0.000, which is below 0.005. (2) There is a positive and significant influence of work environment variables on the performance of employees of Perumda Air Minum Tirta Sewakadarma Denpasar City. This is evidenced by the value of tcount > ttable, namely 11.076 > 2.000 with a probability value (significance) = 0.000, which is below 0.005. (3) There is a positive and significant influence of motivation and work environment variables on the performance of Perumda Air Minum Tirta Sewakadarma Denpasar City employees. This is evidenced by the value of Fcount > Ftabel, namely 60.589 > 3.15 with a probability value (significance) = 0.000, which is below 0.005.